Nominal Wage Rigidity: Non-Parametric Tests Based on Union Data for Canada - Louis Christofides; Thanasis Stengos (Center for Economic Studies and ifo Institute (CESifo), 2001)
We study the wage-change distributions in union contractsreached in Canada between 1976-1999. We use non-parametric tests to check for nominal wage rigidity and find that it is present during low inflation periods.
Keywords: 330; Nominal wage rigidity; non-parametric tests